2010
DOI: 10.1007/s12185-010-0738-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell neoplasm: biology and pathology

Abstract: Natural killer (NK) cell neoplasm is a heterogeneous disease group. In the latest World Health Organization (WHO) classification of tumours of hematopoietic and lymphoid tissues (2008), disease entities considered as NK-cell derivation include NK-lymphoblastic leukemia/lymphoma, chronic lymphoproliferative disorders of NK cells, aggressive NK-cell leukemia, and extranodal NK-cell lymphoma, nasal-type. Despite recent advances in NK-cell research, which have expanded our understanding of the biology of NK-cell n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…The disease is more prevalent among Asians and Native Americans as compared with the populations in the western countries [13]. In the majority of cases, this disease occurs in the nasal cavity and other parts of the upper aerodigestive tracts.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is more prevalent among Asians and Native Americans as compared with the populations in the western countries [13]. In the majority of cases, this disease occurs in the nasal cavity and other parts of the upper aerodigestive tracts.…”
Section: Introductionmentioning
confidence: 99%
“…These observations, along with the characteristic morphology and cytogenetic findings in the present case, indicated that the disease was consistent with the features of leukemic BPDCN. The main differential diagnosis for leukemic BPDCN is acute leukemia of ambiguous lineage, particularly the provisional entity NK-cell lymphoblastic leukemia/lymphoma (NK-LL/L) (4,13). Based on the 2008 WHO classification (4), in cases where BPDCN is excluded, the diagnosis of NK-LL/L may be considered when absence of B-cell or myeloid cell markers, negative TCR gene rearrangement and expression of CD56 with immature T-associated markers (such as cytoplasmic-CD3, CD7 and CD2) are observed (4).…”
Section: Case Reportmentioning
confidence: 99%
“…Cytotoxic molecules such as TIA1, granzyme B, and perforin are positive. CD43 is commonly expressed, and occasional cases are positive for CD30 [16].…”
Section: Figure 2 H Isto P Ath Olo Gic C H a Racterization And Im M mentioning
confidence: 99%
“…Most NKTCLs derive from NK-cell lineage, whereas NK-like cytotoxic T-cell derivation is postulated in a minor population of this disease because tumor cells express a part of the T-cell markers and show a TCR gene rearrangement [16,17], Of the 4 TCR gene complexes, the TRG@ is the most suitable for diagnostic PCR, as it consists of only 4 V gene families with 16 gene segments and 5 J gene segments, which can all be covered by a small number of primers [18]. We adopted a highly sensitive multiplex PCR method and analyzed the amplified PCR products by heteroduplex capillary electrophoresis, which is more sensitive and specific than conventional gel electrophoresis [10].…”
Section: Figure 2 H Isto P Ath Olo Gic C H a Racterization And Im M mentioning
confidence: 99%